2017
DOI: 10.1186/s12936-017-1912-y
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine efficacy for Plasmodium vivax in Myanmar in populations with high genetic diversity and moderate parasite gene flow

Abstract: Background Plasmodium vivax malaria remains a major public health burden in Myanmar. Resistance to chloroquine (CQ), the first-line treatment for P. vivax, has been reported in the country and has potential to undermine local control efforts.MethodsPatients over 6 years of age with uncomplicated P. vivax mono-infection were enrolled into clinical efficacy studies in Myawaddy in 2014 and Kawthoung in 2012. Study participants received a standard dose of CQ (25 mg/kg over 3 days) followed by weekly review until d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The present study showed that all samples were fixed at K76T and A220S mutations in pfcrt , but remained wild type at the pfmdr1 N86 and D1246. The high prevalence of mutations in pfcrt gene may be the result of continued drug pressure of CQ for treating P. vivax infections in Myanmar [ 64 ]. In pfmdr1 gene, Y184F had a frequency of 23.3% and there was no statistically significant association between Y184F and the day-3 parasite-positive and -negative phenotypes ( P = 1.000, Fisher’s exact test).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that all samples were fixed at K76T and A220S mutations in pfcrt , but remained wild type at the pfmdr1 N86 and D1246. The high prevalence of mutations in pfcrt gene may be the result of continued drug pressure of CQ for treating P. vivax infections in Myanmar [ 64 ]. In pfmdr1 gene, Y184F had a frequency of 23.3% and there was no statistically significant association between Y184F and the day-3 parasite-positive and -negative phenotypes ( P = 1.000, Fisher’s exact test).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine and PQ are still the drugs of choice for the treatment of P. vivax in some countries, especially in Latin America [ 28 31 ]. However, CQRPv has emerged in several parts of the world [ 32 , 33 ], including Malaysia [ 30 ], Myanmar [ 34 ], India [ 33 ] and Brazil [ 7 , 35 ]. The molecular mechanism of CQRPv is still not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…In the GMS, although CQ remains generally effective for the treatment of P. vivax cases [13][14], there have been sporadic reports of CQR P. vivax in most GMS countries. CQR P. vivax malaria has been documented in Myanmar as early as in 1993 [15][16][17], and in recent years clinical failures after CQ treatment have been reported in multiple regions of Myanmar [18,19]. Although the recurrent rates of P. vivax infections within 28 days of CQ treatment remained low in Vietnam (3.5%) and western Thailand (8%) [14,21], CQR P. vivax isolates have been confirmed in these areas [20,21].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%